Knowledge Attitude and Practice of Dental Professionals Towards Diabetes Mellitus in Islamabad Dental Hospital - Muhammad Jamal Awan; Maham Ishtiaq Raja; Maryam Tahir; Laiba Seher; Muhammad Mudassar Saleem; Abdul Manan Shahid; Khalid Mahmood Saddiqi (Gandhara University, 2022)
OBJECTIVES The aim of this study was to determine general dentists and dental students knowledge, attitudes and practices regarding diabetes mellitus, a major public health issue with oral complications. METHODOLOGY This cross-sectional study design was conducted in Islamabad dental hospital for three months on House officers and final year BDS students. A convenience sampling technique was used for the sample. A pretested questionnaire was selected from the previous study. After approval of the IRB, the questionnaires were distributed among participants of the research. The descriptive analysis of the collected data was done by using SPSS software version 20. RESULTS The overall results of knowledge of dentists towards diabetes scored high (90%), 80% of the respondents had a positive attitude towards diabetes mellitus. Less than half (20%) of the dentists scored poor in the practice of diabetes mellitus, while about three fourth of the respondents had a good score (80%). CONCLUSION Dentists in Islamabad dental hospital have good knowledge and practice skills regarding diabetes. The attitude of the dental practitioners in Islamabad dental hospital regarding diabetes is also positive.